A study of the prebiotic-like effects of tomato juice consumption in rats with diet-induced non-alcoholic fatty liver disease (NAFLD). Issue 10 (6th September 2017) - García-Alonso, F. J.; González-Barrio, R.; Martín-Pozuelo, G.; Hidalgo, N.; Navarro-González, I.; Masuero, D.; Soini, E.; Vrhovsek, U.; Periago, M. J.
Abstract : Tomato juice intake partially ameliorated high-fat diet-induced disturbances of gut microbiota, particularly by increasing Lactobacillus abundance and diminishing the acetate to propionate ratio. Abstract : Gut microbiota may play a role in the pathogenesis of NAFLD. We investigated whether tomato juice consumption for 5 weeks could ameliorate high-fat diet-induced alterations in certain intestinal bacterial groups and products arising from their metabolism (short-chain fatty acids and microbial phenolic catabolites). For this, we used a rat model with NAFLD induced by a high-fat diet, involving four experimental groups: NA (standard diet and water), NL (standard diet and tomato juice), HA (high-fat diet and water) and HL (high-fat diet and tomato juice). The onset of NAFLD impacted the gut microbiota profile, reducing the abundance of Bifidobacterium and Lactobacillus and increasing that of Enterobacteriaceae . Also, reduced concentrations of propionate, butyrate and phenolic catabolites and an increased acetate to propionate (Ac : Pr) ratio were observed. Tomato juice intake partially ameliorated high-fat diet-induced disturbances, particularly by increasing Lactobacillus abundance and diminishing the Ac : Pr ratio, suggesting a potential improvement of the metabolic pattern of NAFLD.